From Ideology to Electability: The Implications of Non-Cadre Candidate Recruitment on PKS's Strategy and Efforts to Become an Open Party - Prayitno, Adi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study discusses the recruitment strategy of non-cadre legislative candidates carried out by the Prosperous Justice Party (PKS) in the 2009 Legislative Election. As a cadre-based party, this step is a significant innovation in the history of PKS. The research uses a qualitative approach with an analytical descriptive method, utilizing in-depth interviews with resource persons and analysis of related documents. The results of the study show that the recruitment policy of non-cadre candidates is influenced by several main factors. First, efforts to increase electability in non-PKS base areas. Second, recruiting figures who are considered capable of making a significant contribution to the party's goals. Third, an experiment to make PKS a more open party. Finally, pragmatic reasons such as the party's financial needs. However, this step caused various criticisms, both from internal and external circles, because it was considered contrary to the principle of the cadre party that prioritized internal cadres. Theoretically, this policy reflects a change in the character of PKS from party ideology to more pragmatic. This research highlights the importance of balancing political pragmatism and ideological consistency in maintaining party cohesion. These findings are relevant to understand the dynamics of political parties in Indonesia, especially in facing the challenges of political modernization.Keywords: Political recruitment, non-cadre candidates, PKS, 2009 elections, cadre parties, political strategy.